Аналіз супутніх ферментативних активностей у термотолерантних штамів мікроміцетів – продуцентів целюлолітичних ферментів - Омельчук, Євген Олександрович; Лапська, Ю. Ю.; Красінько, Вікторія Олегівна; Айзенберг, Вікторія Леонідівна; Стойко, Вікторія Іштванівна (My University, 2012)
The analysis of the related enzymatic activites ( poligalacturonase, pectinesterase, inulinase) among termotolerance micromicetes of the different taxonomic groups that have high endoglucanase activity was carried out. Stains, that can be used as a potential of cellulosolitic enzymes that have complex and directional activity were defined.
Keywords: термотолерантні мікроміцети; целюлази; полігалактуроназа; пектинестераза; інуліназа; termotolerance micromicetes; cellulase; poligalacturonase; pectinesterase; inulinase; кафедра біотехнології і мікробіології